Imaging analysis for muscle stem cells and regeneration - Karthikeyan, Smrithi; Asakura, Atsushi (Frontiers in Cell and Developmental Biology, 2024)
Composed of a diverse variety of cells, the skeletal muscle is one of the body's only tissues with the remarkable ability to regenerate after injury. One of the key players in the regeneration process is the muscle satellite cell (MuSC), a stem cell population for skeletal muscle, as it is the source of new myofibers. Maintaining MuSC quiescence during homeostasis involves complex interactions between MuSCs and other cells in their corresponding niche in adult skeletal muscle. After the injury, MuSCs are activated to enter the cell cycle for cell proliferation and differentiate into myotubes, followed by myofibers to regenerate muscle. Despite decades of research, the exact mechanisms underlying MuSC maintenance and activation remain elusive. Traditional methods of analyzing MuSCs, including cell cultures, animal models, and gene expression analyses, provide some insight into MuSC biology but lack the ability to replicate the 3-dimensional (3-D) in vivo muscle environment and capture dynamic processes comprehensively. Recent advancements in imaging technology, including confocal, intra-vital, and multiphoton microscopies, provide promising avenues for dynamic MuSC morphology and behavior to be observed and characterized. This chapter aims to review live-imaging methods that have contributed to uncovering insights into MuSC behavior, morphology changes, interactions within the muscle niche, and internal signaling pathways during the quiescence to activation (Q-A) transition. Integrating advanced imaging modalities and computational tools provides a new avenue for studying complex biological processes in skeletal muscle regeneration and muscle degenerative diseases such as sarcopenia and Duchenne muscular dystrophy (DMD).